Lymphoepithelial cyst of the parotid in HIV negative individual: a case report - Amatya, Paras Raj; Limbu, Tilak Raj; Baral, Sovit Jung; Bastakoti, Shankar (Journal of Chitwan Medical College, 2019)
Benign Lymphoepithelial cyst (BLEC) of parotid gland are more common in HIV positive patients and is rare in HIV negative individuals. We present a 16-year-old HIV negative female who presented with a painless, gradually increasing swelling in the left parotid region. Excisional biopsy was done and HPE showed benign lymphoepithelial cysts. The rarity of this lesion in a HIV negative patient is the main reason for reporting this case.